Theoretical asthma self-management program for Taiwanese adolescents with self-efficacy, outcome-expectancy, health behaviour, and asthma symptoms: A randomized controlled trial - Tzu-Jung Tseng, RN PhD; Chiung-Jung (Jo). Wu, RN DrHlthSc FACN; Anne M. Chang, RN PhD FRCNA (Contemporary Clinical Trials Communications, 2020)
Background: The asthma prevalence of Taiwanese adolescents continued to rise. With physical and psychological changes in adolescents, managing asthma can be quite challenges and affect social, emotional and physical wellbeing. Adolescents with high self-efficacy levels are more likely to be involved in prevention and management activities. The aim of this study was to develop an effective asthma self-management program taking account for adolescents' developmental stages and based on Bandura's self-efficacy model. Methods: A two-arm, parallel group, randomized controlled trial was used. The outcomes were self-efficacy, outcome-expectancy, asthma prevention and self-management behaviour, and controlling asthma symptoms. Translation and back-translation process were used for original tools in English. Good consistent reliabilities of Chinese versions tools were identified. A t-test or Mann-Whiney U test was employed to determine any mean differences of outcome variables between groups overtime. Results: A sample of 83 patients completed the study. The mean age was 14.2 years (SD = 1.8). Approximately 56.6% of the participants were males. 73% of participants (n = 61) had a mild to intermittent level of asthma severity. Significant improvements were found on self-efficacy, t = −2.8; outcome-expectancy, U = 646, prevention behaviours, t = −3.5, and management behaviours, t = −3.2, but non-significant results for the outcome of asthma control, U = 716. Conclusions: The results provided evidence to support the efficacy of the asthma self-management program. The findings indicated the program improved adolescents’ self-confidence in managing their asthma symptoms. Future clinical practice should consider delivering an educational program using multifaceted and interactive learning strategies.